OSCE Insights 2020: Corona, War, Leadership Crisis - Institute for Peace Research and Security Policy at the University of Hamburg (Nomos Verlagsgesellschaft mbH & Co. KG, 2020)
The contributions to the 2020 edition of OSCE Insights examine the various crises the OSCE faced during that year. Themes include the efforts of the Minsk Group to manage the conflict over Nagorno-Karabakh and the implications of anti-coronavirus measures for the OSCE Code of Conduct on Politico-Military Aspects of Security. Furthermore, authors analyse OSCE conflict cycle tools, the OSCE’s role in the fight against antisemitism, the increasingly limited space for supporting democratic police governance in Central Asia, trust-building in the field of arms control, societal views on the conflict in Eastern Ukraine, relations between the OSCE and the Council of Europe, and Kazakhstan’s aspirations for hosting a connectivity center. With contributions byAndrew Baker, Cornelius Friesendorf, Frank Evers, André Härtel, Marietta König, Sebastian Mayer, Michael Raith, Filip Ejdus, Alexandre Lambert, Thomas Schmidt, Marina Dolcetta Lorenzini, Anna Hess Sargsyan, Philip Remler, Richard Giragosian, Sergey Rastoltsev and Benjamin Schaller. [German version]  [Russian version]